Characterization of Heterogeneous MRSA and MSSA with Reduced Susceptibility to Chlorhexidine in Kuwaiti Hospitals - Vali, Leila; Dashti, Ali A.; Mathew, Febine; Udo, Edet E. (Frontiers in Microbiology, 2017)
Abstract The objective of this investigation was to identify the lineages of MRSA and MSSA with reduced susceptibility to chlorhexidine in Kuwaiti hospitals. 121 clinical MRSA and 56 MSSA isolates were included in this study. Antimicrobial susceptibility testing was performed for a selection of agents including chlorhexidine and resistance genes were amplified and sequenced. PFGE, spa typing and MLST were completed for a selection of isolates. The results showed SCCmec II, III, IV and V were present in 0.8%, 21.5%, 69.4% and 8.3% of the MRSA isolates. agr-1Sa was the most prevalent type in both MSSA (48%) and MRSA (54%). 45% of MRSA contained pvl and 39% contained lukE-lukD, however, as many as 86% of MSSA contained pvl and 96.4% contained lukE-lukD. qac A-C genes were identified in 12.3% of MRSA, norA was present in 82.6% and blaZ in 94.2%. Among MSSA only 5.4% harboured qacA, 83% contained norA and 91% blaZ. Multi-drug resistant ST239/t945 lineage containing a qac gene was the most identified S. aureus. However, other lineages, including ST772-MRSA-V/t4867/pvl(+)qacC/smr and non-qac harbouring lineages of ST217-MRSAIV/t3244/pvl(˗), ST34-MSSA/t161/pvl(+), ST5-MSSA/t688/pvl(+), ST5-MSSA/t4867/norA(+) and ST672-MSSA/t003/pvl(˗), also showed reduced susceptibility to chlorhexidine. The observed reduced susceptibility of non-qac dependent MSSA isolates to chlorhexidine suggests the involvement of other elements in promoting higher MBC (≥30mg/L). Our results confirm that monitoring MSSA is essential as they may have the potential to survive low level biocide exposure.